Estimating measures of interaction on an additive scale for preventive exposures - Knol, Mirjam J.; VanderWeele, Tyler J.; Groenwold, Rolf H. H.; Klungel, Olaf H.; Rovers, Maroeska M.; Grobbee, Diederick E. (European journal of epidemiology, 2011)
Measures of interaction on an additive scale (relative excess risk due to interaction [RERI], attributable proportion [AP], synergy index [S]), were developed for risk factors rather than preventive factors. It has been suggested that preventive factors should be recoded to risk factors before calculating these measures. We aimed to show that these measures are problematic with preventive factors prior to recoding, and to clarify the recoding method to be used to circumvent these problems. Recoding of preventive factors should be done such that the stratum with the lowest risk becomes the reference category when both factors are considered jointly (rather than one at a time). We used data from a case-control study on the interaction between ACE inhibitors and the ACE gene on incident diabetes. Use of ACE inhibitors was a preventive factor and DD ACE genotype was a risk factor. Before recoding, the RERI, AP and S showed inconsistent results (RERI = 0.26 [95% CI: -0.30; 0.82], AP = 0.30 [95% CI: -0.28; 0.88], S = 0.35 [95% CI: 0.02; 7.38]), with the first two measures suggesting positive interaction and the third negative interaction. After recoding the use of ACE inhibitors, they showed consistent results (RERI = -0.37 [95% CI: -1.23; 0.49], AP = -0.29 [95% CI: -0.98; 0.40], S = 0.43 [95% CI: 0.07; 2.60]), all indicating negative interaction. Preventive factors should not be used to calculate measures of interaction on an additive scale without recoding.